PENGARUH E-SERVICE QUALITY DAN PERCEIVED VALUE TERHADAP CUSTOMER LOYALTY - Nugraheni, Rury; Dirgantari, Puspo Dewi; Widjadjanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The purpose of this research is to find out the influence of e-service quality and perceived value on customer loyalty in member of online retail Alfacart in Jawa Barat. A total of 200 respondents were using probability sampling. A questionnaire was used a research instrument to collect data from respondents. The analisis technique used is a verification technique using of structure equation model (SEM). The research shows that e-service quality and perceived value has an influence on customer loyalty